Secondary trait and index selection determination for maize genotype selection in acidic tidal swamp environment - SUWARTI SUWARTI; MUNIF GHULAMAHDI; DIDY SOPANDIE; TRIKOESOEMANINGTYAS TRIKOESOEMANINGTYAS; EKO SULISTYONO; MUHAMMAD AZRAI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Suwarti, Ghulamahdi M, Sopandie D, Trikoesoemaningtyas, Sulistyono E, Azrai M. 2022. Secondary trait and index selection determination for maize genotype selection in acidic tidal swamp environment. Biodiversitas 23: 4169-4179. Determining secondary traits as complementary selection in maize genotypes for abiotic stress environment is compulsory since yield-based selection usually provides biased result. This study aimed to obtain secondary traits for maize selection in an abiotic multi-stresses of Fe, Al, and temporary flooding environments of acid sulfate tidal swamp land using multivariate analysis. A total of 150 (un-repeated) maize inbred lines and five check genotypes in five replicates were arranged in a randomized augmented plot design in three environments to generate 525 single plots. Three types of environments based on irrigation regimes were applied on acid soil tidal swamp land to study the agronomic characteristics of maize genotypes in each environment. Saturated Cultivation Technology (SSC) was considered the optimal environment. Dryland treatment was the condition to let the irrigation only depend on rainwater. Temporary flooding treatment was carried out at five stages of different growth periods. Several steps of analysis were applied in this study by taking variance, and heritability was used as the basis for selections. The characters affected by treatments with medium to high heritability were then analyzed with correlation and pathway analysis. Seven selection indexes, SSI, GMP, YSI, YI, TOL, STI, and MP, that have a high correlation to yield in both optimum and stress environments, were applied simultaneity with the selected trait characters to screen the genotypes utilizing PCA biplot analysis. Venn analysis was used to group the genotypes based on the result of the analysis. Indices of STI, MP, GMP, and traits of rows number per ear and the weight of 6 ears were selected as secondary characters for the maize genotypes selection in Saturated Soil culture with temporary flooding stress. Meanwhile, STI, MP, and ear stand height were the selected characters in the dryland of acid sulfate tidal swamp land. Based on the combination of all secondary character selection, genotypes were grouped into five types of stress tolerance in SSC+TF and DL environments. Eight genotypes were tolerant to both SSC+TF and DL stress, and two genotypes were susceptible to both environments.